(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: The rapid shallow breathing indexe is crucial considering the weaning of patients inprolonged mechanical ventilation. Objective: The purpose of the present study was to compare the high and low rapid shallow breathingindexes with weaning of patients in prolonged mechanical ventilation. Methodology: This cohort study was conducted in the Department of Anesthesia, Pain Palliative &Intensive Care Unit of Dhaka Medical College Hospital, Dhaka, Bangladesh from January 2014 toDecember 2015 for a period of two (02) years. Patients of ICU on mechanical ventilation more than 48hours with the age of 18 to 60 years were included in this study. Standard weaning criteria was consideredas resolution of the primary cause of respiratory failure, state of alertness, cooperation, response tocommands and Glasgow coma scale (GCS) scores ³9. Primary and daily setting of ventilators and thedecision to weaning of the patient was made by the ICU consultants. RSBI was then measured. Thedecision of weaning was not influenced by the RSBI. After measuring RSBI, patients was separatedfrom mechanical ventilator and given T-piece trial (1 to 4 hours) and finally extubated as per advice ofICU consultant and observed for 48 hours. The patients were divided in two groups low RSBI £105breath/min/L and high RSBI >105breath/min/L. These patients were prospectively followed up to 48hours in ICU and HDU. Result: A total of 117 patients were included in this study. The mean age was found 35.42±13.66 yearswith range from 18 to 60 years. The mean mechanical ventilation was found 9.6±6.4 days in low RSBIgroup and 8.6±4.5 days in high RSBI group (p>0.05). The association between RSBI and success inweaning of the patients was recorded. In low RSBI group 94.6% patient’s sustained extubation (success)and high RSBI group 76.0% patients’ sustained extubation. Success was significantly higher in patientswith low RSBI group (p=0.001). The association between RSBI and weaning failure of the patients wasmeasured. In high RSBI group failure was 6(24.0%) and success was 19(76.0%). On the other hand inlow RSBI group failure was found 5(5.4%) and success was 87(94.6%) (p=0.011). Conclusion: In conclusion significant association is found between high and low rapid shallow breathingindexes with weaning of patients in prolonged mechanical ventilation. JBSA 2020; 33(1): 10-15